PENGARUH TRANSFORMATIONAL LEADERSHIP, EMPLOYEE ADAPTABILITY TERHADAP KINERJA KARYAWAN DENGAN WORK ENGAGEMENT SEBAGAI VARIABEL INTERVENING DI CV PALUGADA SEJAHTERA SIDOARJO - Cakra Ragatra Putra; I Dewa Ketut Raka Ardiana (Nirta Learning Centre, 2026)
This study aims to examine and analyze the influence of transformational leadership and employee adaptability on employee performance through work engagement as an intervening variable among employees of CV Palugada Sejahtera Sidoarjo. By managing these three elements, the company is expected to enhance work participation, strengthen employees’ adaptive capacity, and encourage overall performance improvement. This research employs a correlational design intended to identify the relationships and the extent of influence among variables without manipulation. The dependent variable in this study is employee performance, while the independent variables consist of transformational leadership and employee adaptability, and the mediating variable is work engagement. The study adopts a quantitative approach, with respondents consisting of all 75 employees of CV Palugada Sejahtera using a saturated sampling technique. Data were collected through questionnaires and analyzed using the SEM-PLS (SmartPLS) method to assess both direct and indirect effects among variables.